(untitled) (Research, Society and Development, 2020)
In Viçosa city, state of Alagoas, many mules are used to remove sand from the Paraíba River, providing it to the building materials trade in the region and helping to combat siltation on the riverbed. They are constantly framed in this dichotomous discussion between human sustainability and animal maltreatment. The research performed in this project was carried out in two stages using data from 13 tutors and their mules working in the extraction of sand from the Paraiba river, evaluating through a pre-structured questionnaire the socioeconomic profile of the tutors and also the wellbeing of the mules through serological and parametric using predefined parameters such as Heart Rate (HR), Body Score (EC), levels of muscle stress, presence of pain and lameness and presence of wounds. Regarding the problem, the Pro-Carroceiros Project from Federal University of Alagoas has been conducting quarterly awareness-raising activities for tutors regarding animal welfare, as well as veterinary assistance activities such as vaccination, devermination, blood tests and clinical care. The paper aims to trace the socioeconomic profile of the tutors and propose a model for assessing the welfare of these animals, based on integrated extension and research activities.